Historical occurrence of whales in Scottish Waters inferred from whaling records. Issue 10 (17th August 2022) - Ryan, Conor; Calderan, Susannah; Allison, Cherry; Leaper, Russell; Risch, Denise
Abstract: Archived logbooks detailing landings at Scottish shore‐based whaling stations between 1903 and 1951 were used to map whale catch locations. Historical distribution and occurrence are inferred and summary statistics on total landings are updated for blue ( Balaenoptera musculus ), fin ( Balaenoptera physalus ), humpback ( Megaptera novaeangliae ), North Atlantic right ( Eubalaena glacialis ), sei ( Balaenoptera borealis ) and sperm ( Physeter macrocephalus ) whales: a total of 9, 996 whales were caught during this period, which is 3.7% higher than previously reported and 25% higher for blue whales. The most frequently caught species were fin and sei whales. Whaling off Scotland in the 1920s contributed to the likely extinction of right whales in the eastern North Atlantic. Blue whales, once regularly hunted to the west of Scotland, are now rarely documented there and North‐east Atlantic whaling appears to have had a significant and lasting impact on sei whales. Analysis of whaling effort indicates that catch rates remained high despite the depletion of some species. This, may be a consequence of two features of Scottish shore‐based whaling: (1) the mixed species catch composition; and (2) the catching of whales as they migrated through Scottish waters. The findings of this study highlight the historical significance of the shelf‐seas around Scotland as a habitat for some species, which was not apparent from previous studies. These results can inform where there may be potential for the recovery of some species in the future. Current major threats in the North Atlantic include entanglement, ship strike and displacement owing to the effects of climate change. The baseline and historical information on distribution and seasonal occurrence examined here is important for informing spatial and temporal measures to reduce these threats. If populations are to recover post‐whaling there is an increasing need to reduce threats such as ship strikes and entanglement, whose magnitude is proportional to whale density.